2016
DOI: 10.1653/024.099.0104
|View full text |Cite
|
Sign up to set email alerts
|

Trichoplusia ni(Lepidoptera: Noctuidae) Survival, Immune Response, and Gut Bacteria Changes after Exposure toAzadirachta indica(Sapindales: Meliaceae) Volatiles

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Furthermore, our study found that P. absoluta 2nd instar larvae treated with the botanicals (neem and garlic) had lower microbial abundance than most of the B. thuringiensis isolates . This finding agrees with previous studies, which showed that higher susceptibility of neem was associated with lower enterobacterial load in T. ni 40 and higher susceptibility to B. thuringiensis was associated with higher enterobacterial loads in Spodoptera exigua Hübner, 1808 (Lepidoptera: Noctuidae) , probably due to the mode of action of B. thuringiensis , which involves the cry proteins 41 , 42 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, our study found that P. absoluta 2nd instar larvae treated with the botanicals (neem and garlic) had lower microbial abundance than most of the B. thuringiensis isolates . This finding agrees with previous studies, which showed that higher susceptibility of neem was associated with lower enterobacterial load in T. ni 40 and higher susceptibility to B. thuringiensis was associated with higher enterobacterial loads in Spodoptera exigua Hübner, 1808 (Lepidoptera: Noctuidae) , probably due to the mode of action of B. thuringiensis , which involves the cry proteins 41 , 42 .…”
Section: Discussionsupporting
confidence: 93%
“…Albeit minimal, there was a reduction in the abundance of these bacteria and a shift in the microbial diversity upon treatment with the B. thuringiensis isolates and the botanicals suggesting gut microbial repression by the treatments. The reduction in key gut bacteria has also been observed in Trichoplusia ni Hübner, 1800 (Lepidoptera: Noctuidae), where treatment with neem volatiles reduced Enterobacteria transcript amplification 40 . Furthermore, our study found that P. absoluta 2nd instar larvae treated with the botanicals (neem and garlic) had lower microbial abundance than most of the B. thuringiensis isolates .…”
Section: Discussionmentioning
confidence: 79%
“…Only one report described assays against the cabbage looper T. ni , where volatile organic compounds from A. indica stems promoted significant neonatal and larval mortality (24 and 77%, respectively) at 1 g doses and an LD 50 of 5.6 g after 7 days ( Table 17 ) [ 71 ].…”
Section: Insecticidal Compounds and Plant Extractsmentioning
confidence: 99%
“…P. interpunctella larvae were reared on a cracked wheat diet (McGaughey and Beeman, 1988) at 25ºC ± 2ºC, 55 ± 10% relative humidity, and 16h light/8h dark photoperiod. For gut bacterial assays, larvae were reared under normal artificial diet (Nuñez-Mejía et al, 2016) (Fig. S1), artificial diet (wheat agar, wheat germ, soy flour and sugar sterilized by autoclave, and vitamin solution sterilized by membrane filtration and added after artificial diet temperature was lower than 60°C), and/or antibiotic treated agar-based artificial diet, where antibiotic solution was sterilized by membrane filtration and added after artificial diet temperature was lower than 60°C.…”
Section: Insect Colonymentioning
confidence: 99%